Cathodal Iontophoresis of Treprostinil Induces a Sustained Increase in Cutaneous Blood Flux in Healthy Volunteers. (24th January 2013) - Blaise, Sophie; Roustit, Matthieu; Hellmann, Marcin; Millet, Claire; Cracowski, Jean‐Luc
Abstract Objective Prostacyclin analogues are the most effective drugs to treat sclerodermic digital ulcers, but their systemic use is limited by their frequent side effects. The authors tested whether the prostacyclin analogues treprostinil and iloprost, delivered by cutaneous iontophoresis, induce sustained vasodilatation. Methods Twenty healthy volunteers received treprostinil by cathodal iontophoresis on the forearm. Skin blood flux was quantified using laser Doppler imaging. Results Treprostinil 250 µM induced an increase in cutaneous vascular conductance AUC80min (31 897 ± 24 390 %BL·min) compared with NaCl 0.9% (P < .005), treprostinil 2.5 µM (P < .005), and treprostinil 25 µM (P < .005). This was confirmed when flux was recorded for up to 10 hours. Systemic and skin tolerance of treprostinil were good. Iloprost was stopped early because of local toxicity. Conclusion Treprostinil cathodal iontophoresis induces a sustained increase in cutaneous blood flow with good local tolerance. This could be investigated as a new local therapy for digital ulcers in scleroderma.